2021
DOI: 10.1002/anie.202105272
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Synthetic Modification Unlocks a 2D‐to‐3D Switch in MOF Breathing Response: A Single‐Crystal‐Diffraction Mapping Study

Abstract: Post-synthetic modification (PSM) of the interpenetrated diamondoid metal-organic framework (Me 2 NH 2 )[In-(BDC-NH 2 ) 2 ](BDC-NH 2 = aminobenzenedicarboxylate) SHF-61 proceeds quantitatively in a single-crystal-to-singlecrystal manner to yield the acetamide derivative (Me 2 NH 2 )-[In(BDC-NHC(O)Me) 2 ] SHF-62. Continuous breathing behaviour during activation/desolvation is retained upon PSM, but pore closing now leads to ring-flipping to avert steric clash of amide methyl groups of the modified ligands. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…have recently reported the PSM of SHF‐61 (SHF=Sheffield Framework), an interpenetrated In MOF which breathes in two dimensions along the crystallographic b and c axes, to yield an acetamide‐modified MOF, SHF‐62. The additional functionality on the pendant group of SHF‐62 induces breathing in a third dimension, due to unfavourable interactions between amide substituents [15] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have recently reported the PSM of SHF‐61 (SHF=Sheffield Framework), an interpenetrated In MOF which breathes in two dimensions along the crystallographic b and c axes, to yield an acetamide‐modified MOF, SHF‐62. The additional functionality on the pendant group of SHF‐62 induces breathing in a third dimension, due to unfavourable interactions between amide substituents [15] …”
Section: Introductionmentioning
confidence: 99%
“…The additional functionality on the pendant group of SHF-62 induces breathing in a third dimension, due to unfavourable interactions between amide substituents. [15] In recent years, increasing attention has been paid to the PSM of integral units of MOF linkers. In 2009, Bauer et al demonstrated the diastereoselective bromination of stilbene-4,4'-dicarboxylate (SDC) linkers in a Zn MOF, however, the reaction required high temperatures, which resulted in degradation and a loss of porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Exposing cp to gas molecules reconstructs the porosity ( cp → op ), which is abruptly filled with guest through an adsorption process . The gas-induced reopening exhibits novel phenomena, inter alia the shape-memory effect, not observed for classical rigid adsorbents such as zeolites, porous carbons, and mesoporous silica . The switchable nature of flexible MOFs manifests as singularities , in isothermal adsorption profiles, which cannot be assigned to any of the isotherm shapes classified by IUPAC .…”
mentioning
confidence: 99%
“…Exposing cp to gas molecules reconstructs the porosity (cp → op) which is abruptly filled with guest through an adsorption process [5] . The gasinduced reopening exhibits novel phenomena [6][7][8][9][10][11][12][13][14][15] , inter alia the shape-memory effect [16][17][18][19][20] , not observed for classical rigid adsorbents such as zeolites, porous carbons, and mesoporous silica. [21] The switchable nature of flexible MOFs manifests as singularities [22,23] in isothermal adsorption profiles, which cannot be assigned to any of the isotherm shapes classified by IUPAC [24] .…”
mentioning
confidence: 99%